African Virtual University : the paradox of the industrialization process of higher education in Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
Why fund the deployment of a technology where, due to lack of infrastructure, it cannot physically function properly? If the objectives put forward by the World Bank, at the origin of the launch of the African Virtual University (AVU) in 1997, are to increase access to higher education in Africa coupled with economies of scale, the question arises as to what democratisation is hoped for when the means that should make it possible simply cannot function due to lack of infrastructure. This is evidenced by the failure of the AVU in economic and pedagogical terms (Loiret, 2007), in contrast to its continued development through its transformation into a pan-African intergovernmental organisation in 2002. Based on the concept of 'hypertelia' developed by Gilbert Simondon (1958) to designate the over-adaptation of a technical object in an environment unsuited to its functioning, this doctoral research proposes to understand the launch of the African Virtual University (AVU) as an anticipated introduction of ICTs and digital culture by the World Bank within traditional universities in sub-Saharan Africa, with the objective of commodising higher education. This objective is supported by the transformation of the AVU into an intergovernmental organisation which generates a myth (Barthes, 1957; Simondon, 1958) characterised by the separation of a primary form from its ideological background, which, thus liberated, can be attached to other forms, articulated to other backgrounds, and become a general trend. The AVU thus acquires a reason to be : to constitute a mythical form capable of conveying concepts that are transformed into tendencies in the form of structures.
Keywords: African Research